Excel applications for investments - Adair, Troy Alton (McGraw-Hill/Irwin, 2006)
This book is meant to assist in the adoption of spreadsheets into the finance classroom. It is intended to serve as either a supplement to a traditional, introductory text on investments or as a stand-alone text for a more advanced course on using spreadsheets in finance.